Robust liner shipping schedule design in service networks with transshipment cut and run decisions - Mi, Yue (2016)
The liner shipping industry has been suffering from poor schedule reliability due to delays in ports and the prevalence of transshipment. Aiming to solve the real-life problem of schedule reliability, this report investigates the design of schedule for liner shipping service networks, addressing the uncertainties in port time due to port congestion and delays in handling, while minimizing the impacts of misconnections of transshipment cargo and late-delivery. In addition to the usual published time, the schedule contains a target arrival time and a newly-introduced latest departure time for each port of call in each service. The target arrival time hedges against the possible waiting time at ports while the latest departure time enables a vessel to “cut and run” without waiting too long for delayed transshipment cargo. The schedule will serve as easy-to-use guidelines and assist quick and quality management decisions without the use of highly compute-intensive operational decision tools. The robustness of the schedule allows vessels to recover a delayed schedule in worst cases. A mixed-integer nonlinear stochastic programming model is formulated. Solution methodology is discussed in general, which includes linearization, approximation, and discretization.